Нелинейные колебательные процессы в колесных экипажах - Михлин, Ю.В.; Митрохин, С.Г. (Прикладная механика, 2010)
The natural damped vibrations of a wheel crew with independent suspension
are considered with allowance for nonlinear characteristics of the suspension springs and
shock absorbers. The vibrations of a wheel crew with the suspension smooth nonlinear characteristics are studied for the model with seven degrees of freedoms. The corresponding skeleton curves and nonlinear normal modes of vibrations are obtained. For the model with two degrees of freedoms (quarter of the wheel crew), which corresponds to axisymmetric vibrations, the nonlinear normal modes are found for the case of non-smooth nonlinear characteristic of shock absorber. Розглянуто вільні затухаючі коливання колісного екіпажу з незалежною підвіскою з урахуванням нелінійних характеристик пружин та амортизаторів підвіски. Досліджено коливання колісного екіпажу з гладкими нелінійними характеристиками підвіски для моделі з 7 степенями свободи. Отримано відповідні скелетні криві і нелінійні нормальні форми коливання. Для моделі з двома степенями свободи (чверть колісного екіпажу), що відповідає симетричним коливанням, знайдено нелінійні нормальні форми у випадку негладкої нелінійної характеристики амортизатора.